Profile of rape victims attending the Karl Bremer Hospital Rape Centre, Tygerberg, Cape Town - Muideen Bello; Michael K. Pather (South African Family Practice)
Background: Given the high prevalence of HIV infection in this country today it is not difficult to observe the risk faced by victims of sexual assault. In addition, there is a lack of available data on the per-episode risk of HIV infection with specific sexual encounters,1 and in combination with poor follow-up of sexual assault victims,2–4 this has resulted in few studies assessing the risk of HIV infection after sexual assault. There is a paucity of research conducted in this field particularly at rape centres in the Cape Metropolitan area of the Western Cape.